Imunoexpressão das proteínas metaloproteinase-1, metaloproteinase-7 e p53 e sua correlação com os fatores prognósticos clínico-patológicos no adenocarcinoma colorreta - Nunes, Benicio Luiz Bulhões Barros Paula [UNIFESP] (2009)
Purpose: To analyse the immunoexpression of metalloproteinase-1, metalloproteinase-7 and also the p53 in colorectal adenocarcinoma and correlate it with the clinical pathological prognostic factors. Methods: Formalin-fixed, wax-embedded tissue of the tumours of 82 patients were analysed by immunohystochemistry through the streptavidin-biotin method, using the tissue microarray technique. When evaluating the positivism of the markers a categorical score was used, which predetermined the cutting value on the percentage of the tumour’s cored cells. The protein’s tissue expressions were correlated with the variation represented by the degree of cellular differential, stage, relapse-free survival, recurrence, survival and specific mortality. The tests of the qui-square and Kaplan-Meyer were applied with the aim to verify the markers association with the studied variations. In order to test the significance of the differences between the curves of relapse-free survival and of the overall survival, the tests of Log-Rank and Wilcoxon were utilized. Results: The metalloproteinase-1 was found to be positive in all the tumours. The metalloproteinase-7 was found to be positive in 50 (61%) and negative in 32 (39%) of the tumours. The p53 was found to be positive in 70 (85.4%) and negative in 12 (14.6 %) of the tumours. The correlation of the markers expressions separately and in conjunction produced any significant statistical data. Conclusion: There was no correlation between immunoexpression of metalloproteinase-1, metalloproiteinase-7 and p53 with recurrence, mortality, relapse-free survival, survival, degree of cellular differential and stage in colorectal cancer.